STRATEGI E-COMMERCE DAN PEMASARAN DIGITAL DALAM PENGEMBANGAN USAHA CAMILAN PANGSIT COKELAT EAT MEE - Berlian Nursyanti Mahardika; Neng Silvi Miladiah; Helen Veranika; Ati Yulyanti; Wulan Meliyawati; Ipan Ipan (CV. Denasya Smart Publisher, 2025)
The rapid digital transformation has significantly impacted Micro, Small, and Medium Enterprises (MSMEs), shifting consumer behavior towards online product search. This presents both challenges and opportunities for the snack industry, which faces intense competition. This study addresses the limited empirical research on digital channel effectiveness in the fast-moving snack sector. The research aims to examine the e-commerce and digital marketing strategies of